2013
DOI: 10.1002/pros.22662
|View full text |Cite
|
Sign up to set email alerts
|

Obesity‐induced diabetes and lower urinary tract fibrosis promote urinary voiding dysfunction in a mouse model

Abstract: BACKGROUND Progressive aging- and inflammation-associated fibrosis effectively remodels the extracellular matrix (ECM) to increase prostate tissue stiffness and reduce urethral flexibility, resulting in urinary flow obstruction and lower urinary tract symptoms (LUTS). In the current study, we sought to test whether senescence-accelerated mouse prone (SAMP)6 mice, which were reported to develop prostatic fibrosis, would also develop LUTS, and whether these symptoms would be exacerbated by diet-induced obesity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 47 publications
5
70
0
2
Order By: Relevance
“…22,[24][25][26][27] Prostatitis, aging, and metabolic diseases such as type 2 diabetes mellitus induce inflammatory changes, which can associate with the development of prostatic fibrosis. 1,5,[14][15][16]19,28 Similarly, in our study prostatic calcification significantly associated with aging ( Table 2). This relationship was also proven in previous studies.…”
Section: Commentmentioning
confidence: 61%
See 1 more Smart Citation
“…22,[24][25][26][27] Prostatitis, aging, and metabolic diseases such as type 2 diabetes mellitus induce inflammatory changes, which can associate with the development of prostatic fibrosis. 1,5,[14][15][16]19,28 Similarly, in our study prostatic calcification significantly associated with aging ( Table 2). This relationship was also proven in previous studies.…”
Section: Commentmentioning
confidence: 61%
“…Recently, prostatic fibrosis, especially periurethral fibrosis, has been suggested as a novel cause of LUTS in men. 1,5,6,8 Since 2012, the periurethral area has been focused on as a key region determining LUTS severity. Ma et al 6 analyzed periurethral tissues obtained from radical prostatectomies and demonstrated that periurethral tissue from men with LUTS was significantly stiffer with higher collagen content and lower glandularity compared with men without LUTS.…”
Section: Commentmentioning
confidence: 99%
“…In an animal model, insulin resistance contributes to detrusor overactivity, which is a possible cause of OAB symptoms [22]. Other investigations showed that obesity and concurrent type 2 diabetes mellitus lower urinary tract fibrosis and are inextricably and biologically linked to urinary voiding dysfunction [23]. However, the effect of irritation on obesity can be postulated based on the assumption that fat in the pelvis reduces bladder expansion and thus increases urinary frequency and determines low mean urinary volumes for micturition, as showed by voiding diaries in our study.…”
Section: Discussionmentioning
confidence: 98%
“…Аналогич-ные данные об усилении фиброза периуретральных отделов ПЖ были получены M. Gharaee-Kermani и соавт. [69] в опытах на мышах, содержащихся на ди-ете, обогащенной жирами, у которых развились ожи-рение и диабет.…”
Section: инсулинорезистентность и гиперинсулинемияunclassified